2022
DOI: 10.3389/fimmu.2022.984508
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid induces intestinal lipid metabolism disorder, endoplasmic reticulum stress and inflammation by affecting phosphatidylethanolamine content in large yellow croaker Larimichthys crocea

Abstract: In the 21st century, intestinal homeostatic imbalance has emerged as a growing health challenge worldwide. Accumulating evidence reveals that excessive intake of saturated fatty acid (SFA) induces intestinal homeostatic imbalance. However, the potential molecular mechanism is still unclear. In the present study, we found that palm oil or palmitic acid (PA) treatment disturbed lipid metabolism homeostasis and triggered endoplasmic reticulum (ER) stress and inflammation in the intestine or intestinal cells of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…PA induces ER stress by increasing the content of saturated ER membrane phospholipids [ 39 ], perturbing ER calcium homeostasis [ 40 ] and modulating protein folding [ 41 ]. Furthermore, the PA treatment induced an inflammatory response, which was consistent with previous studies [ 24 , 27 , 28 , 29 , 30 ]. A study reported that dietary palm oil that contained a high level of PA could increase the inflammatory response by activating the TLR–NF-κB pathway [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PA induces ER stress by increasing the content of saturated ER membrane phospholipids [ 39 ], perturbing ER calcium homeostasis [ 40 ] and modulating protein folding [ 41 ]. Furthermore, the PA treatment induced an inflammatory response, which was consistent with previous studies [ 24 , 27 , 28 , 29 , 30 ]. A study reported that dietary palm oil that contained a high level of PA could increase the inflammatory response by activating the TLR–NF-κB pathway [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Palm oil (PO) is enriched with PA and is widely used as a substitute for fish oil in aquaculture [ 25 ]. Previous studies have shown that the overuse of PO often induces inflammation [ 26 , 27 ]; meanwhile, PA has been revealed to induce inflammation and ER stress [ 28 , 29 , 30 ]. However, the relationship between GRP78 and TM/PA-induced inflammation or ER stress is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipids are key components of all cellular and subcellular membranes and essential for membrane function and integrity. 153,154 Moreover, phospholipids, as conduction signaling of intestinal inflammatory factors, participate in the maintenance of metabolic and immune homeostasis and the inhibition of the inflammatory response, 155 and the pathogenesis of type 2 diabetes, 156 fatty liver disease and schizophrenia-related behaviors. 157,158 Phospholipids are divided into phosphoglycerides and sphingomyelin (SM).…”
Section: Dietary Lipids and Intestinal Homeostasismentioning
confidence: 99%
“…169 PC affects the intestinal environment mainly by promoting the distribution of the gut microbiota, enhancing the intestinal barrier, 169 promoting intestinal development, and regulating the intestinal immune function. 155,170 Mice lacking PC exhibit reduced mucin secretion in the intestinal epithelial cells and necrotic apoptosis in goblet cells; 171 this suggests that the increase in PC content is conducive to maintain intestinal phospholipid homeostasis and cellular integrity. 171…”
Section: Dietary Lipids and Intestinal Homeostasismentioning
confidence: 99%
“…An increasing number of studies are showing that ER stress contributes to the progression of various diseases, including obesity, cancer, degenerative disorders, and immune-mediated diseases ( 10 , 11 ). Dysregulated ER stress is related to inflammation ( 12 ). It is widely established that sepsis is a systemic inflammatory response, and the core mechanism of initiation and progression of sepsis is inflammation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%